Peer Verbal Encouragement Is More Effective than Coach Encouragement in Enhancing CrossFit-Specific 1-RM Strength, Functional Endurance, and Psychophysiological Assessment Performance - Amir Romdhani; Faten Sahli; Omar Trabelsi; Mahmoud Rebhi; Hatem Ghouili; Hajer Sahli; Atef Salem; Khaled Trabelsi; Haitham Jahrami; Achraf Ammar; Makram Zghibi (Sports, 2024)
This study compares the effects of coach verbal encouragement (CVE) and peer verbal encouragement (PVE) on CrossFit-specific one-repetition maximum (1-RM) strength, functional endurance, and psychophysiological assessments. A total of 36 sports science students (18 males, 18 females; mean age: 21.3 ± 0.5 years) participated in a randomized, counterbalanced crossover study in which 1-RM strength and endurance assessment sessions were undertaken under PVE, CVE, and no verbal encouragement (NVE) on separate days. Here, 1-RM strength was assessed through squat, deadlift, and bench press exercises, while endurance was evaluated using 8 min time trials (8MTT). Following the physical assessments, psychophysiological evaluations were conducted using the Borg Rating of Perceived Exertion (RPE) and the Feeling Scale (FS). The findings revealed that, after PVE, all the 1-RM strength test, 8MTT, RPE, and FS values exhibited significant increases compared to those of CVE (p [<0.001–<0.01], r = −0.84 [large]) and NVE (p [<0.001–<0.05], r [−0.43–0.52] [small]). Exceptions were noted in 1-RM-deadlift (p > 0.05, r = −0.43 [small]) and 1-RM-bench-press (p > 0.05, r = −0.43 [small]), where CVE demonstrated higher scores (1-RM-squat, 8MTT, RPE, and FS) (p [<0.001–<0.05], r = −0.64 [large]) in comparison to NVE. In conclusion, the study established that PVE is more impactful than CVE in enhancing CrossFit-specific 1-RM strength, functional endurance, and psychophysiological assessment performance. These findings suggest that coaches/teachers should consider involving their athletes in the reinforcement process for evaluated peers. This collaborative approach may not only optimize performance outcomes but also foster a supportive and motivational training environment.